2009
DOI: 10.1097/jtn.0b013e3181ac921f
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal Behavior After a Traumatic Event

Abstract: This article reviews the literature on the psychosocial and psychiatric consequences (such as a diagnosis of posttraumatic stress disorder and elevated suicide risk) for a range of traumatic life experiences, including military combat, criminal victimization, interpersonal and domestic violence, child abuse and neglect, sexual retraumatization, natural disasters, torture, and the Holocaust. Possible mechanisms mediating the relationship between trauma and suicide are presented along with suicide risk assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 87 publications
(70 reference statements)
1
17
0
1
Order By: Relevance
“…These observations suggest that strict comparisons of rates between countries should be interpreted with caution, as not only are estimates affected by ascertainment procedure but also by when the estimates are made. Conversely, traumatic event and suicidality may have shared environmental risk factors leading to both traumatic event and suicidality (35). This may seem paradoxical, given that those studies had also reported lifetime estimates.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These observations suggest that strict comparisons of rates between countries should be interpreted with caution, as not only are estimates affected by ascertainment procedure but also by when the estimates are made. Conversely, traumatic event and suicidality may have shared environmental risk factors leading to both traumatic event and suicidality (35). This may seem paradoxical, given that those studies had also reported lifetime estimates.…”
Section: Discussionmentioning
confidence: 97%
“…Traumatic events may expose an individual to mental and physical disorders which in turn lead to suicidality. Conversely, traumatic event and suicidality may have shared environmental risk factors leading to both traumatic event and suicidality (35).…”
Section: Africa and Have Used Different Ascertainment Proceduresmentioning
confidence: 99%
“…The relationship between trauma exposure and later suicidal behavior is widely reported in the literature (Belik, Stein, Asmundson, & Sareen, 2009;Dube et al, 2001;Krysinska, Lester, & Martin, 2009). Yet the basis for this relationship is not entirely clear.…”
Section: Abstract Suicidality Posttraumatic Stress Cumulative Traumamentioning
confidence: 96%
“…Because there is a lack of concrete evidence, opinions are divided on the role and possible mechanisms of blast waves in causing neurotrauma, and the resultant effects on the central and peripheral nervous systems [91]. What is not debated is the effect traumatic brain injury can have psychologically, resulting in depression, substance abuse, personality disorder and sharing many of the same clinical features as post-traumatic stress disorder [92,93]. The current role of neural stem cells in dictating cognitive behavior is unclear, but they are a key component of neurogenesis and have been linked to post-traumatic stress disorder [94], stress-triggered depression [95] and other common aspects of mental health [96].…”
Section: Auxiliary Applicationsmentioning
confidence: 99%